2006
DOI: 10.1002/chem.200500921
|View full text |Cite
|
Sign up to set email alerts
|

Novel 2,1,3‐Benzothiadiazole‐Based Red‐Fluorescent Dyes with Enhanced Two‐Photon Absorption Cross‐Sections

Abstract: This paper reports the two-photon absorbing and orange-red fluorescence emitting properties of a series of new 2,1,3-benzothiadiazole (BTD)-based D-pi-A-pi-D-type and star-burst-type fluorescent dyes. In the D-pi-A-pi-D-type dyes 1-6, a central BTD core was connected with two terminal N,N-disubstituted amino groups via various pi-conjugated spacers. The star-burst-type dyes 8 and 10 have a three-branched structure composed of a central core (benzene core in 8 and triphenylamine core in 10) and three triphenyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
139
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(146 citation statements)
references
References 114 publications
5
139
2
Order By: Relevance
“…[25] All the compounds give relatively high fluorescence quantum yields (Φ PL ) in dichloromethane solution: 0.6 for 1, 0.55 for 2, 0.30 for 3, and 0.35 for 4 (Rhodamine B as the standard, Φ PL = 0.65 in ethanol). [3] Figure 4. Room-temperature uncorrected emission spectra of 3 and 4 in heptane, dioxane, THF, dichloromethane, and MeCN at 1 ϫ 10 -6  (λ ex 3: 412 nm; 4: 450 nm).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…[25] All the compounds give relatively high fluorescence quantum yields (Φ PL ) in dichloromethane solution: 0.6 for 1, 0.55 for 2, 0.30 for 3, and 0.35 for 4 (Rhodamine B as the standard, Φ PL = 0.65 in ethanol). [3] Figure 4. Room-temperature uncorrected emission spectra of 3 and 4 in heptane, dioxane, THF, dichloromethane, and MeCN at 1 ϫ 10 -6  (λ ex 3: 412 nm; 4: 450 nm).…”
Section: Resultsmentioning
confidence: 98%
“…[3,4] The EL and NLO performances of these molecules are effectively dependent on their HOMO-LUMO or band gaps associated with intramolecular D-A interactions. The strength of D-A interactions is determined by donor and acceptor groups and the connecting π bridges.…”
Section: Introductionmentioning
confidence: 99%
“…The red shift of the charge transfer band in 6 compared to 4 and 7 is consistent with the trend observed for 2,1,3-benzothiadiazole-based D-A-D type compounds. [18,19] Apparently, the non-coplanarity between phenylene and phenazine in 4 results in less effective interaction between the donor and the acceptor. Relative to the para-substitution in 6, the metasubstitution of the peripheral diphenylamines in 7 seems to deconjugate [20] the effective interaction between the amines and the phenazine.…”
Section: Synthetic Strategymentioning
confidence: 99%
“…Through this study, it is found that the calculated results reproduce very well the corresponding experimental data [87]. In order to study the emission properties of P3HT2BTCz compounds, the TD/B3LYP method was applied to the geometry of the lowest singlet excited state optimized at the CIS level with 3-21G* basis set [124]. The normalized photoluminescence (PL) spectrum of P3HT2BTCz (Fig.…”
Section: Optical Properties and Electronic Structuresmentioning
confidence: 71%